Evaluating the Educational Impact of Digital Storytelling through Student Perceptions - Ahada, Ichi; Surya, Satyawaty; Rusmawaty , Desi; Hermagustiana , Istanti; Wardani, Ida (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Digital storytelling can strengthen relations between participants (N. G. Davey & Benjaminsen, 2021; N. Davey & Moulton, 2020). This research intends to connect people around the world to build networking and collaboration to create stories but for the first step, the focus is intended to cooperate with students in the classroom to write a story together by combining ideas and creativity. Reading, writing, and sharing are the main activities conducted by participants. It is the participant’s turn to read the previous paragraph, add another paragraph, and share it with the other participant. Since this research was intended to find out how students/participants’ perceptions of experiencing digital storytelling, a quantitative approach was employed as the research design. Using digital storytelling to engage students in meaningful learning experiences is a useful strategy. It develops teamwork, creativity, and writing abilities. Students find the storytelling process more engaging and enjoyable when technology is used to improve it. The study''s conclusions show that students view digital storytelling favorably because it inspires them to use their imaginations, work with others, and become better writers